Notes on Zohn’s Translation of Benjamin’s “Die Aufgabe des Übersetzers” - Rendall, Steven (TTR)

(untitled) (Association canadienne de traductologie, 1997)
AbstractZohn's translation of Benjamin's "Die Aufgabe des Übersetzers" — In 1968 Harry Zohn published a pioneering translation of "Die Aufgabe des Übersetzers" that for many years was the only form in which Benjamin's famous essay was known to most readers in English. These notes examine certain problems raised by Zohn's translation.